O1-S11.02 Determinants of time trends in HIV prevalence in the young antenatal population of Karnataka districts. (10th July 2011) - Mahajan, U; Banandur, P; Rajaram, S; Duchesne, T; Abdous, B; Ramesh, B M; Moses, S; Alary, M
Abstract : Background: In 2003, the Bill & Melinda Gates Foundation initiated a focused HIV prevention program (India AIDS Initiative: Avahan) among high-risk and bridge groups. We studied determinants of time trends in HIV prevalence among young (<25 years) antenatal (ANC) women caused by these intensive prevention intervention (IPI) program compared to non-intensive intervention (Non-IPI) program. Methods: Random intercept multilevel models were developed using logistic regression (xtmelogit command) to examine effects of IPI, program and district level variables on HIV prevalence among young ANC women. Data from annual sentinel surveillance of ANC women were used as individual level characteristics. Selected program and socio-demographic variables at district level were included as distal variables. Interaction between time and intensity of program intervention was assessed. Results: HIV prevalence in young ANC women decreased steadily from 1.4% to 0.77% from 2003 to 2007, and increased to 0.83% in 2008 (Adjusted OR (AOR)=0.59, (95% CI):0.45% to 0.77%). Rural (AOR=0.87, 95% CI: 0.76% to 0.99%) and literate women (AOR=0.76, 95% CI:0.66% to 0.87%) had lower risk of HIV compared to urban and illiterate women respectively. Presence of major truck halt points (AOR=1.57, 95% CI: 1.17% to 2.12%) in the district was associated with high risk of HIV. Higher age at marriage was associated with lower risk of HIV (AOR=0.85, 95% CI: 0.78% to 0.93%). There was significant interaction between time and intensity of intervention. In the years 2006 and 2007, Non-IPI districts had a significantly higher risk of HIV compared to IPI districts (AOR2006=1.86, 95% CI: 1.18% to 2.93% and AOR 2007=2.25, 95% CI: 1.39% to 3.62%) respectively. Among the program variables regular contact with high risk group was associated with slightly reduced risk of HIV (AOR=0.998, 95% CI: 0.996% to 0.999%) see Abstract O1-S11.02 table 1 . Conclusion: HIV prevalence in ANC population declined significantly in IPI districts from 2003 to 2008 compared to non-IPI districts in Karnataka. IPI had a definite impact on reduction of HIV prevalence in general population during 2006 and 2007. This coincides with the maturity of IPI during 2006 and 2007 along with the initiation of NACP-III in 2007. Learning from IPI might have influenced National AIDS Control Program-III implementation in non-IPI districts in Karnataka leading to similar effects in IPI and non-IPI districts in 2008. Improving female literacy and increasing the age at marriage would help favour reduction of HIV.